(untitled) (Conference Zone, 2022)
Acculturation is the process of changing the material culture, customs, and beliefs that result from the direct interaction and interaction of different socio-cultural systems. Acculturation is based on communicative processes. Just as ethnic minorities acquire their cultural characteristics as a result of their interactions with one another, ethnic minorities also learn about new cultural contexts and acquire new skills through communication..